Enhancement Literacy Finance As A Key Factor In Realize Development Sustainable At The Destination Business Tour Religion - Amelia Setyawati; Puji Handayati; Arief Noviarakhman Zagladi (International Journal of Management Research and Economics, 2023)
The complexity and importance of the role of the religious tourism business in a global context, where spiritual and religious destinations not only attract tourists, but also become centers of economic and cultural activities. The success of a religious tourism business destination depends not only on its spiritual appeal, but also on the manager's ability to understand and manage financial aspects wisely. The importance of increasing financial literacy in the context of the religious tourism business is increasingly visible due to the various challenges faced by the tourism industry, including climate change, changes in consumer behavior and global market dynamics. Recognizing the financial literacy gap in the religious tourism business can be integrated into education and training programs for industry players. The method used in this research is a qualitative research approach with a descriptive research type, to observe the extent to which MSME business actors in the Wali Sembilan religious tourism area understand and can apply financial literacy to increase their business success. This research took place in the Wali Sembilan religious tourism area. Based on results reduction observations, interviews and documentation that have been done interpret it can stated that enhancement literacy finance become factor key in realize development sustainable destination business tour Wali Sembilan religion. Profile perpetrator diverse businesses _ in literacy finance show necessity effort increase, especially among MSMEs as _ bone back economy populist. Enhancement literacy finance give impact positive on ability perpetrator business in make decision smart finances, planning _ investing, and managing risk, create environment stable and powerful business _ competitive. Therefore _ that 's necessary done steps strategic like strengthening literacy programs finance, cooperation between government and private, and integration literacy finance in curriculum education For support continuity economy and business in the destination that.